Odpowiedzi

2010-02-24T21:23:01+01:00
A) 6x-24-2=6x-26
b) 2x+2-x+1
c) -3y+6+4y+8=y+14
d) 5x-5y-5-4x-8=x-5y-13
e) 6a+2b-2a+2b=4a+4b
f) 2x-2-2x=-2
g) x'do kwadratu'-x-3x'do kwadratu'-x=-2x'do kwadratu'-2x
h)5a'do kwadratu'-15a-3a'kwadrat'+15 = 2a'do kwadratu'
2010-02-24T21:29:26+01:00
A) 6(x-4)-2
6x-24-2
6x-26
b) 2(x+1)-(x-1)
2x+2-x+1
x+3
c) -3(y-2)+4(y+2)
-3y+6+4y+8
y+14
d) 5(x-y-1)-4(x+2)
5x-5y-5-4x-8
x-5y-13
e) 2(3a+b)-2(a-b)
6a+2b-2a+2b
4a+4b
f) 1/2(4x-4)-2x
2x-2-2x
-2
g)x(x+1)-3
x2+ x-3
h)5a(a-3)-3a(a-5)
5a(kwadrat)-15a-3a(kwadrat)+15
2a(kwadrat)
2010-02-24T21:52:11+01:00
A) 6(x-4)-2 =
= 6x - 24 - 2 =
= 6x - 26

b) 2(x+1)-(x-1) =
= 2x + 2 - x + 1 =
= x + 3

c) -3(y-2)+4(y+2) =
= -3y + 6 + 4y + 8 =
= y + 14

d) 5(x-y-1)-4(x+2) =
= 5x - 5y - 5 - 4x - 8 =
= x - 5y - 13

e) 2(3a+b)-2(a-b) =
= 6a + 2b - 2a + 2b =
= 4a + 4b

f) 1/2(4x-4)-2x =
= 2x - 2 - 2x =
= -2

g) x(x-1)-3(x'do kwadratu'-x) =
= x² - x - 3x² + 3x =
= -2x² + 2x

h) 5a(a-3)-3a(a-5) =
= 5a² - 15a - 3a² + 15a =
= 2a²

;-))